Unveiling the complex double-edged sword role of exosomes in nasopharyngeal carcinoma - Xueyan Huang; Yuedi Tang (PeerJ)
Nasopharyngeal carcinoma (NPC) is a malignancy arising from the epithelium of the nasopharynx. Given its late diagnosis, NPC raises serious considerations in Southeast Asia. In addition to resistance to conventional treatment that combines chemotherapy and radiation, NPC has high rates of metastasis and frequent recurrence. Exosomes are small membrane vesicles at the nanoscale that transport physiologically active compounds from their source cell and have a crucial function in signal transmission and intercellular message exchange. The exosomes detected in the tissues of NPC patients have recently emerged as a potential non-invasive liquid biopsy biomarker that plays a role in controlling the tumor pathophysiology. Here, we take a look back at what we know so far about the complex double-edged sword role of exosomes in NPC. Exosomes could serve as biomarkers and therapeutic agents, as well as the molecular mechanisms by which they promote cell growth, angiogenesis, metastasis, immunosuppression, radiation resistance, and chemotherapy resistance in NPC. Furthermore, we go over some of the difficulties and restrictions associated with exosome use. It is anticipated that this article would provide the reference for the apply of exosomes in clinical practice.